Haryana State Draft Annual Plan 1990-91 Vol. III (In 4 Volumes) - Planning Commission (Planning Commission, 1990)
As outlay of 3.41858 lkhs was approved in the Ureic Five Year Plan tor Major Medium and Multipurpose River Valley project. Cut of this Ps. 41862 lakhs was for major medium irrigation schemes, and R (-) 12 lakhs for Multipurpose River Valley Project viz. Unit-I and II of the Project, With ’the Dabs Project Unit III all has practically been Completed, as such a nominal provision of I (-) 12 lakhs was made to account for Haryana’s share in. the receipts from this project under Irrigation components. No provision during 10 9 0-91 has been proposed.
Government of Haryana
Planning Department Government of Haryana
Keywords: Irrigation and Power Sectors; Industries; Transport and Communication Sectors; Multipurpose Projects; Major and Medium Irrigation; Minor Irrigation; Flood Control & Drainage; Command Area Development Authority; Power Projects; including Power Portion of multipurpose projects; Industry and Minerals; Civil Aviation; Roads and Bridges; Environment